In vitro and ex vivo vanadium antitumor activity in (TGF-β)-induced EMT. Synergistic activity with carboplatin and correlation with tumor metastasis in cancer patients. (May 2016) - Petanidis, Savvas; Kioseoglou, Efrosini; Domvri, Kalliopi; Zarogoulidis, Paul; Carthy, Jon M.; Anestakis, Doxakis; Moustakas, Aristidis; Salifoglou, Athanasios
Graphical abstract: Highlights: Inhibition of (TGF-β)-mediated EMT by vanadium. Reduction of mitochondrial Δ ψ m in malignant cells triggers EMT blockade. Ex vivo down-regulation of CD24/CD44/CD133 CSC markers in cancer patients. Synergism between vanadium and carboplatin triggers G0 /G1 cell cycle arrest. Synergistic mechanism sensitizes tumor cells to carboplatin-induced apoptosis. Abstract: Epithelial to mesenchymal transition (EMT) plays a key role in tumor progression and metastasis as a crucial event for cancer cells to trigger the metastatic niche. Transforming growth factor-β (TGF-β) has been shown to play an important role as an EMT inducer in various stages of carcinogenesis. Previous reports had shown that antitumor vanadium inhibits the metastatic potential of tumor cells by reducing MMP-2 expression and inducing ROS-dependent apoptosis. However, the role of vanadium in (TGF-β)-induced EMT remains unclear. In the present study, we report for the first time on the inhibitory effects of vanadium on (TGF-β)-mediated EMT followed by down-regulation of ex vivo cancer stem cell markers. The results demonstrate blockage of (TGF-β)-mediated EMT by vanadium and reduction in the mitochondrial potential of tumor cells linked to EMT and cancer metabolism. Furthermore, combination of vanadium and carboplatin (a) resulted in synergistic antitumor activity in ex vivo cell cultures, and (b) prompted G0 /G1 cell cycle arrest and sensitization of tumor cells to carboplatin-induced apoptosis. Overall, the findings highlight the multifaceted antitumor action of vanadium and its synergistic antitumor efficacy with current chemotherapy drugs, knowledge that could be valuable for targeting cancer cell metabolism and cancer stem cell-mediated metastasis in aggressive chemoresistant tumors.